Total Factor Productivity Revisited: A Dual Approach to Development Accounting - Shekhar Aiyar; Carl-Johan Dalgaard (University of Copenhagen, Economic Policy Research Unit (EPRU), 2004)
This paper tackles a number of issues that are central to cross-country comparisons of productivity. We develop a dual method to compare levels of total factor productivity (TFP) across nations that relies on factor price data rather than the data on stocks of factors required by standard primal estimates. Consistent with the development accounting literature based on primal estimates, we find that TFP accounts for the bulk of differences in income per worker across countries. However, we also find that there are significant differences between TFP series calculated using the two different approaches. We trace the reason for this divergence to inconsistencies between the data on user costs of capital and physical stocks of capital. In addition, we establish that the standard Cobb-Douglas methodology of assuming a constant capital share of one-third for all countries is a very good approximation to a more general formulation under which countries have different aggregate production functions which do not require a constant elasticity of substitution between factors.
Keywords: O47; O57; 330; TFP; development accounting; dual approach; Cobb-Douglas hypothesis; Produktivität; Arbeitsproduktivität; Wirtschaftswachstum; Theorie